2017
DOI: 10.18632/oncotarget.20010
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factor 3 contributes to the malignancy of glioma via regulating HIF-1α

Abstract: Trefoil factor 3 (TFF3) plays significant roles in several solid tumors. However, the expression pattern and function of TFF3 in glioblastoma (GBM) have not been reported. Here, we report that expression level of TFF3 significantly elevated in glioma and correlated with the prognosis of glioma patients. Then we found TFF3 promotes proliferation, invasion, and migration and inhibits apoptosis of glioma cells in vitro, and delayed tumor progression in subcutaneous xenograft nude mice, and prolonged the median su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Furthermore, TFF3 has been implicated in reduced sensitivity and acquired resistance to chemo-, hormonal, and targeted therapies in different cancers; and in particular, mammary carcinoma with acquired trastuzumab resistance exhibited a shift in oncogene addiction from HER2 to TFF3 8,10,21 . As TFF3 exhibits increased expression in various cancers to promote cancer progression, therapeutic resistance, and relapse, and is associated with poor patient survival, it is a potential actionable target in cancer 9,1113,33,34 . Hence, we have designed a novel small-molecule inhibitor of TFF3, AMPC (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TFF3 has been implicated in reduced sensitivity and acquired resistance to chemo-, hormonal, and targeted therapies in different cancers; and in particular, mammary carcinoma with acquired trastuzumab resistance exhibited a shift in oncogene addiction from HER2 to TFF3 8,10,21 . As TFF3 exhibits increased expression in various cancers to promote cancer progression, therapeutic resistance, and relapse, and is associated with poor patient survival, it is a potential actionable target in cancer 9,1113,33,34 . Hence, we have designed a novel small-molecule inhibitor of TFF3, AMPC (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia elicits nuclear accumulation of HIF‐1α, which binds to the consensus HRE sequence located within the TFF3 promoter 7 . Knockdown of TFF3 reduced the expression of HIF‐1α in a hypoxia‐independent manner 29 . Considering their tight relationship to both ER and HIF, we first noticed that there was a significant correlation between CA12 and TFF3.…”
Section: Discussionmentioning
confidence: 89%
“…Knockdown of TFF3 reduced the expression of HIF-1α in a hypoxiaindependent manner 29 . Considering their tight relationship to both ER and HIF, we first noticed that there was a significant correlation ESR1 on protein level.…”
Section: Discussionmentioning
confidence: 99%
“…However, VHL-defective ccRCC cell lines display unexpectedly variable sensitivity to HIF-2α-targeted therapies [ 11 ], which provide effective treatment for only a subset of patients [ 140 ]. Mechanistically, phosphorylation of HIF-1α has been demonstrated to enhance transactivation of target genes by either disrupting its interaction with VHL and thereby stabilizing HIF-1α, or by increasing the affinity of HIF-1α for transcriptional coactivators [ 141 ]. We showed that CK2 associates with and retains its catalytic activity towards HIF-2α, suggesting a functional link between them.…”
Section: Discussionmentioning
confidence: 99%